Evaluation of Bacilus Thuringiensis Berliner and Baculovirus Heliothis as microbial control agents of Heliothis Armigera (Hubner) and Spodoptera Littoralis (Boisduval) on tomata. - Lutwama, Julian Julius (Obafemi Awolowo University, 2023)
69P